IMPLEMENTATION OF THE INTEGRATED LEARNING MODEL TO ENHANCE CONCEPTUAL UNDERSTANDING AND THE CHARACTER OF RESPECTING DIFFERENCES AMONG ELEMENTARY SCHOOL STUDENTS - Realita, Rona Dear; Laksana, Dek Ngurah Laba (STKIP Citra Bakti, 2026)
This study aimed to analyze the effectiveness of implementing the integrated learning model in integrating Civics, Social Studies, and Mathematics for second-grade elementary school students. The research employed Classroom Action Research (CAR) conducted in three meetings involving 18 students of grade II SD VITA in the 2025/2026 academic year. Data were collected through observation, students’ worksheets, reflective activities, pre-test and post-test scores, and documentation. Data analysis was carried out descriptively qualitative and quantitative by comparing students’ learning outcomes and participation during the learning process. The results showed that the implementation of integrated learning successfully improved students’ cognitive achievement and social character. The average pre-test score increased from 72.2 to 90.8 in the post-test. In addition, students demonstrated better collaboration, empathy, and appreciation for differences through group discussions and contextual data visualization activities. The integration of local wisdom and concrete learning media also enhanced students’ engagement and understanding. Therefore, the integrated learning model proved to be effective in creating meaningful, contextual, and holistic learning experiences for elementary school students.